2014
DOI: 10.1002/lt.23982
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letter to the Editors

Abstract: TO THE EDITORS:We thank dos Santos Schraiber et al. 1 and Lai and Lerut 2 for their interest and comments regarding our study on applying alpha-fetoprotein (AFP) >1000 ng/ mL as an exclusion criterion for liver transplantation (LT) for hepatocellular carcinoma (HCC).3 dos Santos Schraiber et al.1 reported their experience with 206 patients receiving transplants for HCC and found that an AFP threshold of 200 ng/mL was predictive of HCC recurrence. They believed that the higher AFP >1000 ng/mL used in our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In France, Duvoux's algorithm is currently in use and an AFP value of 1000 ng/mL is recognized as a limit over which a LT should not be performed. The UCSF team now applies a similar policy [62] . What about the values in between 15 and 1000 ng/mL?…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
See 1 more Smart Citation
“…In France, Duvoux's algorithm is currently in use and an AFP value of 1000 ng/mL is recognized as a limit over which a LT should not be performed. The UCSF team now applies a similar policy [62] . What about the values in between 15 and 1000 ng/mL?…”
Section: Defining a Cut-off Value For Afpmentioning
confidence: 99%
“…These studies enabled AFP to be part of the definition of a successful downstaging, along with radiological features. In fact, Yao et al [62] in California require that patients with an initial AFP > 1000 ng/mL have AFP decreased to < 500 ng/mL after loco regional therapy, before undergoing LT. Similarly, in Yamashiki et al [43] 2004 93 United States Prospective 100 ng/mL Drop-out from list Shetty et al [42] 2004 109 United States Retrospective 300 ng/mL Recurrence, death Todo et al [54] 2007 653 Japan Retrospective 200 ng/mL Recurrence 1000 ng/mL Parfitt et al [61] 2007 75 Canada Retrospective 1000 ng/mL Recurrence Pérez-Saborido et al [44] 2007 95 Spain Retrospective 200 ng/mL Recurrence Onaca et al [10] 2007 902 United States Retrospective 200 ng/mL Recurrence Adler et al [86] 2008 226 Belgium Retrospective 100 ng/mL Recurrence Zou et al [45] 2008 303 China Retrospective 1000 ng/mL Fatal recurrence Ioannou et al [50] 2008 5028 United States Retrospective 455 ng/mL Death Xu et al [46] 2009 97 China Retrospective 400 ng/mL Recurrence Toso et al [49] 2009 6478 Canada Retrospective 400 ng/mL Death Lao et al [55] 2009 124 United States Prospective 1000 ng/mL Recurrence Xiao et al [87] 2009 224 China Retrospective 800 ng/mL Death McHugh et al [47] 2010 101 United States Retrospective 100 ng/mL Recurrence, death Levi et al [88] 2010 244 United States Retrospective 100 ng/mL Recurrence Merani et al [66] 2011 6817 United States Retrospective 400 ng/mL Death Lai et al [89] 2011 153 Italy Retrospective 210 ng/mL Recurrence Mailey et al [48] 2011 2253 United States Retrospective 400 ng/mL Death Muscari et al [28] 2012 122 France Retrospective 500 ng/mL Recurrence, death Ciccarelli et al [65] 2012 137 Belgium Retrospective 400 ng/mL Recurrence Wong et al [59] 2013 211 United States Retrospective 400 ng/mL Recurrence Harimoto et al [90] 2013 167 Japan Retrospective 300 ng/mL Recurrence Abdel-Wahab et al [68] 2013 170 Egypt Retrospective 200 ng/mL Recurrence, death Grąt et al [67] 2014 121 Poland Retrospective 100 ng/mL Recurrence Hameed et al [30] 2014 211 United States Retrospective 1000 ng/mL Microvascular invasion Lee et al [91] ...…”
Section: Evolution Of Afp Over Time: a Critical Markermentioning
confidence: 99%
“…Such datum is not in line with other experiences, in which the adoption of specific models based on AFP values showed a reduction in transplantable patients ranging from 4.7% to 6.2% . In the latter cases, a very high AFP cut‐off (>1000 ng/ml) was used, with the obvious intent to simultaneously reduce the HCC recurrence rate and to avoid excluding too many patients from LT without post‐LT recurrence …”
Section: Discussionmentioning
confidence: 77%
“…23,24 In the latter cases, a very high AFP cut-off (>1000 ng/ml) was used, with the obvious intent to simultaneously reduce the HCC recurrence rate and to avoid excluding too many patients from LT without post-LT recurrence. 25 Another confirmation of the fact that AFP should be used in combination with imaging derives from the sub-analysis focused on the impact of the AFP delta-slope in different subgroups of patients according to the mRECIST status after LRT. The higher AFP discriminative ability was observed in patients with tumour progression: this can be explained by the consideration that AFP levels are strongly influenced by successful or unsuccessful LRTs.…”
Section: Discussionmentioning
confidence: 99%
“…Starting from this statement, different equations able to define AFP modification have been proposed. The San Francisco transplant center underlined the recent implementation in their inclusion policy for LT to include patients with AFP levels > 1000 ng/mL only if LRT enabled to decrease this level beneath 500 ng/mL [21] . A Canadian study including 48 patients showed by 1901 July 28, 2015|Volume 7|Issue 15| WJH|www.wjgnet.com McHugh et al [12] 2010 101 United States 100 Grąt et al [13] 2014 121 Poland 100 Abdel-Wahab et al [14] 2013 170 (LDLT) Egypt 200 Lai et al [15] 2011 153 Italy 210 Harimoto et al [16] 2013 167 (LDLT) Japan 300 Merani et al [6] 2011 6817 United States 400 Toso et al [7] 2009 6478 United States 400 Zheng et al [8] 2008…”
Section: From Static To Dynamicmentioning
confidence: 99%